1999
DOI: 10.1128/jvi.73.7.5637-5645.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Protective Epitopes (Protectopes) in the Central Conserved Domain of a Prototype Human Respiratory Syncytial Virus G Protein

Abstract: A recombinant fusion protein (BBG2Na) comprising the central conserved domain of the respiratory syncytial virus subgroup A (RSV-A) (Long) G protein (residues 130 to 230) and an albumin binding domain of streptococcal protein G was shown previously to protect mouse upper (URT) and lower (LRT) respiratory tracts against intranasal RSV challenge (U. F. Power, H. Plotnicky-Gilquin, T. Huss, A. Robert, M. Trudel, S. Stahl, M. Uhlén, T. N. Nguyen, and H. Binz, Virology 230:155–166, 1997). Panels of monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 54 publications
3
36
0
1
Order By: Relevance
“…In contrast two doses of 20 µg of P40-Cys G144 -159 (N -terminal coupling) were poorly immunogenic and no lung protection was observed. Similar results were obtained when BB was used for conjugation, indicating that the results were independent of the carrier protein [28]. Using this panel of monoclonal antibodies and synthetic peptides, the structural elements of G2Na implicated in protective efficacy were mapped and five different B-cell epitopes (145-159, 164-176, 171-187, 172-187 and 190-204) were identified (Figure 4(B)), covering the highly conserved cystine nose domain [28,29].…”
Section: Immuno-chemical Characterization Of G2na: B and T-cell Epitosupporting
confidence: 76%
See 2 more Smart Citations
“…In contrast two doses of 20 µg of P40-Cys G144 -159 (N -terminal coupling) were poorly immunogenic and no lung protection was observed. Similar results were obtained when BB was used for conjugation, indicating that the results were independent of the carrier protein [28]. Using this panel of monoclonal antibodies and synthetic peptides, the structural elements of G2Na implicated in protective efficacy were mapped and five different B-cell epitopes (145-159, 164-176, 171-187, 172-187 and 190-204) were identified (Figure 4(B)), covering the highly conserved cystine nose domain [28,29].…”
Section: Immuno-chemical Characterization Of G2na: B and T-cell Epitosupporting
confidence: 76%
“…Similar results were obtained when BB was used for conjugation, indicating that the results were independent of the carrier protein [28]. Using this panel of monoclonal antibodies and synthetic peptides, the structural elements of G2Na implicated in protective efficacy were mapped and five different B-cell epitopes (145-159, 164-176, 171-187, 172-187 and 190-204) were identified (Figure 4(B)), covering the highly conserved cystine nose domain [28,29]. Using the PEPSCAN technology, there was a noticeable absence of reactivity with the 12-mer peptides spanning the cysteine-rich region but the corresponding epitope was unambiguously identified using the correctly folded synthetic G4 hexadecapeptide.…”
Section: Immuno-chemical Characterization Of G2na: B and T-cell Epitosupporting
confidence: 76%
See 1 more Smart Citation
“…BBG2Na is a recombinant chimeric protein comprised of BB (the albumin binding domain of Streptococcal protein G) and G2Na (residues 130-230 of the RSV-A Long strain G protein) expressed in E. coli. In pre-clinical studies, we found that BBG2Na formulated in alum was immunogenic and protective against RSV-A and -B challenges , was immunogenic and protective in murine neonates, even in the presence of high anti-RSV maternal antibody titers (Brandt et al, 1997;Siegrist et al, 1999), did not induce evidence of enhanced pathology (Corvaia et al, 1997;Plotnicky-Gilquin et al, 1999b;Power et al, 2001a), and protected via antibodies and CD4 + T cells (Plotnicky-Gilquin et al, 1999aPower et al, 2001b).…”
Section: Recombinant Hybrid Rsv Vaccine (Ultan F Power Centre D'immmentioning
confidence: 94%
“…In animals polyclonal antibodies generated either to virus infection or to wild type or recombinant G glycoprotein have little sub‐group cross reactivity [Stott et al, ; Johnson et al, ; Walsh et al, ; Murata and Catherman, ] and following primary infection of human infants, only lineage specific antibodies to the G glycoprotein were detected in the convalescent sera [McGill et al, ]. However, Plotnicky‐Gilquin et al [] have demonstrated that antibody responses to a synthetic peptide corresponding to the central conserved motif do occur both in hyperimmunized mice and in older human convalescents and Palomo et al [] have demonstrated antibodies which compete with monoclonal antibodies to this region in a number of human sera. Where present such responses may be beneficial as anti‐G MAbs, generated in several laboratories and whose epitopes overlap this motif, have been shown to be protective in both cotton rats and mice reducing virus replication and, independently, pulmonary inflammation [Walsh et al, ; Plotnicky‐Gilquin et al, ; Collarini et al, ; Haynes et al, ; Miao et al, ].…”
Section: Introductionmentioning
confidence: 99%